ONLINE GAMBLING FROM THE PERSPECTIVE OF SHARIA ECONOMIC LAW AND ITS NEGATIVE PSYCHOLOGICAL IMPACT - Prakoso, Firza Agung; Hakim, Edi Lukman; Ramdhani, Reviandy Azhar (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
Online gambling is increasingly prevalent among the Indonesian population, with a wide range of online gambling products available and popular across nearly all levels of society. Legally, gambling in Indonesia is considered an illegal activity, and individuals who engage in it may face criminal sanctions in accordance with the applicable laws and regulations. In practice, online gambling is typically conducted in private locations, given that gambling is regarded as an unlawful act and may result in criminal penalties. This study employs a qualitative approach using a literature review method. The types of online gambling commonly played can be categorised into nine groups: online poker, domino QQ, online football betting, capsa susun, virtual sports, online e-games betting, number games, online ceme dealers, and blackjack. From an Islamic perspective, gambling is clearly prohibited (haram), and the profits derived from gambling are considered usury (riba). Participation in gambling is often influenced by environmental factors, such as interactions with dealers or peers who also gamble, thereby encouraging involvement. Additionally, the motivation to gamble can stem from internal factors, such as an individual’s personal desire to attain wealth rapidly.